1990
DOI: 10.1093/brain/113.3.721
|View full text |Cite
|
Sign up to set email alerts
|

Familial Cerebral Amyloid Angiopathy With Nonneuritic Amyloid Plaque Formation

Abstract: Two families have been described previously with the features of an autosomal dominant familial cerebral amyloid angiopathy with nonneuritic plaque formation. The clinical features of the cases were dementia, spastic paralysis and ataxia. It has now been established that both families were descended from a common ancestor and the case histories of 26 affected individuals in 5 generations of this pedigree are reported. An autopsy study has been performed on a recent case. The findings are described and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 0 publications
3
112
1
Order By: Relevance
“…Familial British dementia (FBD), 1 an autosomal dominant neurodegenerative disorder, is characterized by progressive spastic tetraparesis, cerebellar ataxia, and dementia (1). The principal pathological hallmarks of FBD include severe amyloid angiopathy, non-neuritic amyloid plaques affecting cerebellum, hippocampus, and cerebral cortex, hippocampal neurofibrillary tangles, and perivascular white matter changes.…”
mentioning
confidence: 99%
“…Familial British dementia (FBD), 1 an autosomal dominant neurodegenerative disorder, is characterized by progressive spastic tetraparesis, cerebellar ataxia, and dementia (1). The principal pathological hallmarks of FBD include severe amyloid angiopathy, non-neuritic amyloid plaques affecting cerebellum, hippocampus, and cerebral cortex, hippocampal neurofibrillary tangles, and perivascular white matter changes.…”
mentioning
confidence: 99%
“…The LTP paradigm we employ takes only 90 min from the initial application of peptide until the end of the experiment and compared with most other commonly used assays of toxicity is relatively rapid. Second, loss of synapses is an early and invariant event in AD and FBD (15,16,42) and is anticipated to be preceded by changes in synaptic function. Indeed, in the case of AD it has been suggested that neuronal loss may occur as a consequence of persistent disruption of plasticity (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Protein masses were acquired over two ranges: 1-10 and 10 -25 kDa, and calibration was performed using insulin (5,735 Da) and myoglobin (16,952 Da), respectively (Bruker, Billerica, MA). Spectra were summed from 2500 laser shots from an Nd:YAG laser operating at 355 nm and 200 Hz, and were acquired with an accepted signal-to-noise ratio set to Ͼ20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both conditions are distinguished by progressive dementia, spasticity and cerebellar ataxia with a neuropathology remarkably similar to that seen in AD, including amyloid deposition in the cerebral vessels, the presence of neuritic, non-neuritic and perivascular amyloid plaques, and NFT. [10][11][12][13] Amyloid deposits in FBD and FDD are made of two newly created amyloid peptides: ABri and ADan. Both peptides derive from mutant forms of the same precursor protein, BriPP, codified by a gene (BRI) located on the long arm of chromosome 13 with a primary structure that resembles a type II single-spanning transmembrane protein.…”
mentioning
confidence: 99%